2018
DOI: 10.25077/dampak.15.1.1-6.2018
|View full text |Cite
|
Sign up to set email alerts
|

Biosorpsi Kromium (Cr) Pada Limbah Cair Industri Elektroplating Menggunakan Biomassa Ragi Roti (Saccharomyces cerevisiae)

Abstract: Electroplating industry is one of the industries producing liquid waste containing heavy metals. Among the heavy metals contained in the liquid waste is Chromium (Cr) which has a high toxicity. One technology that can be applied to eliminate Cr metal in liquid waste is by the method Biosorption using biomass derived from yeast bread (Saccharomyces cerevisiae). This study aimed to study the ability of bread yeast biomass (saccharomyces cerevisiae) in removing Cr metal on variations in biosorbent weight of 0.25;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
1
0
1
Order By: Relevance
“…Adsorption Cu(II) performed by (Setiawan et al, 2019) showed an efficiency of 55.36%. As for the adsorption of Cr(II) conducted by (Elystia et al, 2018), the highest efficiency is 54.7%. From these two studies, it can be noted that Saccharomyces cerevisiae is effective enough to remove heavy metals with an average percentage of about 50%.…”
Section: The Effect Of Phmentioning
confidence: 99%
“…Adsorption Cu(II) performed by (Setiawan et al, 2019) showed an efficiency of 55.36%. As for the adsorption of Cr(II) conducted by (Elystia et al, 2018), the highest efficiency is 54.7%. From these two studies, it can be noted that Saccharomyces cerevisiae is effective enough to remove heavy metals with an average percentage of about 50%.…”
Section: The Effect Of Phmentioning
confidence: 99%
“…Hal tersebut dikarenakan tidak ada perbedaan penyerapan yang berarti antara biomassa yang hidup ataupun mati. Biomassa yang sudah mati memiliki kelebihan dalam proses penyerapan logam berat yakni biomassa yang telah mati tidak memerlukan penambahan nutrisi dalam penyerapannya (Elystia et al, 2018).…”
Section: Padaunclassified